Razgovor s vlast'iu . Razgovor s vlast'iu . Talk with the Power . Разговор с властью - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the Head of the Soviet of Federation, Vladimir Shumeiko, at his home. Featured in the program: Shumeiko, Vladimir Filippovich (Chairman of the Federation Council) Интервью с председателем Совета Федерации, Владимиром Шумейко, у него дома. В программе участвуют: Шумейко, Владимир Филиппович (Председатель Совета Федерации)